Urban strategy playground: Rethinking the urban planner's toolbox. (March 2020) - Seifert, Nils; Mühlhaus, Michael; Petzold, Frank
This article presents the results of the Urban Strategy Playground research group. Over the last 5 years, the focus of an interdisciplinary team of researchers was the conception, implementation and evaluation of a decision-support system for inner-city urban and architectural planning. The overall aim of past and ongoing research is to enable planners to validate and compare possible planning measures based on objective criteria. The Urban Strategy Playground software framework is an expandable toolbox that supports planners in developing strategies, evaluating them and visually preparing them for political decision-making processes and public participation. Examples of implemented tools are the simulation and monitoring of building codes, analysis of key density indicators and green space provision, simulation of shading, building energy and noise dispersion. For visualising the planning results, the framework provides interfaces for rapid prototyping of haptic models, as well as web viewers and a connection to Augmented Reality applications. Core aspects of the system were evaluated through case studies in cooperation with urban planning offices, housing companies and municipalities, proving feasibility, high acceptance of the decision-support software, and need for more tailored tools.